Curr??culo e complexidade: marcas multirreferenciais - Passos, Rita Margareth Costa (2017)
The investigation, of a qualitative nature, based upon the study of complexity, especially by means of Edgar Morin??s Complex Thought and Edgar Morin??s and Jacques Ardoino???s Multireferentiality, respectively and stimulated by the Diretrizes Curriculares Nacionais (DCN) [National Curriculum Guidelines] for the Pedagogy courses ??? undergraduate degree ??? presents the curriculum of the Pedagogy courses of two communitarian institutions, PUC-SP ??? Pontif??cia Universidade Cat??lica ??? SP [Pontifical Catholic University - S??o Paulo] and UCSAL-BA ??? Universidade Cat??lica de Salvador-BA ??? [Catholic University of Salvador-Bahia] as the object of investigation, with the objective to elucidate the marks of multireferentiality which are present in the projects and practices of the professors of these courses. Therefore we collected information about the proposed thematic framework and about the field of investigation in the research collection, in the documents and on the sites of the institutions which were the research object. We also collected the professors?? testimonies by means of the application of semi-structured interviews, which were conducted with a total number of eight professors in their working environment. Using the hermeneutic interpretation and its prerogatives, we carried out the data analysis by considering the elements of multireferentiality as marks: plurality, heterogeneity, authorisation, negatricity, implication and alteration, among other marks revealed in the texts. In the hermeneutic analysis, we ascertained that the projects and practices of the professors of the pedagogy courses of PUC-SP and UCSAL-BA attend the legal determinations by presenting a curriculum configuration which is marked by the plurality of the theoretic and practical knowledge, by the heterogeneity of the school groups and that they assure space so that the subjects-authors of the curriculum, the professors and the students, can develop themselves in a continuous process of dialogue, authorisation, negation, implication and alteration. The results of the research will contribute to the broadening of the study of complexity in the field of education, to the deepening of the multi-referential curriculum, as well as they will be able to favour reflections on the educational practices carried out in the framework of higher education.